(untitled) (Revista Kriterion, 2021)
This article starts from the analysis of the work “La sfida della convivenza” (2018), by Italian philosopher Alberto Pirni, to establish with it a dialogue around the principle of fraternity. In his essay, Pirni offers an essential lexicon to discuss the possibilities of social coexistence between different individuals, groups, communities and cultures in contemporary societies. The first part of the article offers a summary of the ideas of the author, who seeks to deepen the meaning of key concepts for the intercultural debate through a prevalently philosophical lens. In the second part, we establish a dialogue between Pirni’s work and the reflections on the principle of fraternity, in its ethical and normative dimensions. The debate is based, above all, on the Italian, French and Brazilian literature about the theme. The central thesis is that the idea of fraternity can serve as guiding principle to the intercultural ethics defended by Pirni, as long as it is stripped of the excluding or reductive logics that still today is attributed to it. In the concluding remarks, we offer a brief reflection on the possibilities of using the idea of fraternity as an intercultural ethical principle around which to structure deliberation spaces within multicultural societies.